2004
DOI: 10.1007/s00438-004-1006-8
|View full text |Cite
|
Sign up to set email alerts
|

Organisation and structural evolution of the rice glutathione S-transferase gene family

Abstract: Glutathione S-transferases (GSTs) comprise a large family of key defence enzymes against xenobiotic toxicity. Here we describe the comprehensive characterisation of this important multigene family in the model monocot species rice [ Oryza sativa(L.)]. Furthermore, we investigate the molecular evolution of the family based on the analysis of (1) the patterns of within-genome duplication, and (2) the phylogenetic relationships and evolutionary divergence among rice, Arabidopsis, maize and soybean GSTs. By in-sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
108
2
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(120 citation statements)
references
References 52 publications
8
108
2
2
Order By: Relevance
“…Subsequent studies with mammalian GSTs showed that this "ligandin" activity was shown with both tetrapyrroles and porphyrins (4,5), with similar activities demonstrated with GSTs from oat plants (6,7). As is the case in animals, GSTs are also encoded by a superfamily of genes in plants such as Arabidopsis (8) and rice (9) and can be grouped into the tau, phi, theta, zeta, lambda, and dehydroascorbate reductase classes (9,10). As part of a long term program, we are engaged in functionally characterizing these proteins in crops, where they have important roles in conjugating herbicides and other agrochemicals with GSH (11).…”
Section: Glutathione Transferases (Gsts)mentioning
confidence: 78%
See 1 more Smart Citation
“…Subsequent studies with mammalian GSTs showed that this "ligandin" activity was shown with both tetrapyrroles and porphyrins (4,5), with similar activities demonstrated with GSTs from oat plants (6,7). As is the case in animals, GSTs are also encoded by a superfamily of genes in plants such as Arabidopsis (8) and rice (9) and can be grouped into the tau, phi, theta, zeta, lambda, and dehydroascorbate reductase classes (9,10). As part of a long term program, we are engaged in functionally characterizing these proteins in crops, where they have important roles in conjugating herbicides and other agrochemicals with GSH (11).…”
Section: Glutathione Transferases (Gsts)mentioning
confidence: 78%
“…Specific classes of GSTs, like the dehydroascorbate reductases and zeta enzymes, have been ascribed roles in ascorbate recycling and tyrosine catabolism, respectively (10,12). However, the natural functions of the large and plant-specific phi (GSTF) and tau (GSTU) proteins, which dominate the superfamily in Arabidopsis and rice (9), are almost entirely unknown.…”
Section: Glutathione Transferases (Gsts)mentioning
confidence: 99%
“…To identify GST genes in Populus trichocarpa, TBLASTN searches of the P. trichocarpa genome database were performed using 53 full-length GST protein sequences of Arabidopsis thaliana (Dixon et al, 2002), 61 of rice (Oryza sativa; Soranzo et al, 2004), and 575 of other plants, animals, fungi, and bacteria (see Supplemental Data Set 1 online). These 689 fulllength GSTs represent 35 classes defined by the NCBI conserved domain database (Marchler-Bauer et al, 2005).…”
Section: Genomic Data Mining Gst Gene Identification and Nomenclaturementioning
confidence: 99%
“…The conjugation of electrophilic molecules to GSH is catalyzed by the action of glutathione S-transferases (GSTs). In plants, GSTs are encoded by a large gene family with approximately 50 members in Arabidopsis (Arabidopsis thaliana) and rice (Oryza sativa; Soranzo et al, 2004;Edwards and Dixon, 2005), highlighting the importance of GS conjugate formation for the metabolism of endogenous compounds and the detoxification of noxious compounds such as herbicides. GS conjugates are predominantly generated in the cytosol, with minor GST activities in the nucleus, chloroplast, and mitochondrion (Dixon et al, 2002;Dixon and Edwards, 2009).…”
mentioning
confidence: 99%